Interpretation of negative results in fine needle aspiration of discrete pulmonary lesions. Issue 11 (November 1986) - Winning, A J; McIvor, J; Seed, W A; Husain, O A; Metaxas, N
Abstract : A retrospective analysis was carried out on a consecutive series of 181 percutaneous fine needle aspiration biopsies of discrete pulmonary lesions, in which the outcome was established in 95%. In primary bronchial carcinoma the technique had a sensitivity of 86%. There was no relationship between the size, location, or radiological appearance of the lesion and the incidence of false negative results. The principal reason for failure to diagnose malignancy was inadequacy of the material provided for cytological examination. For metastatic neoplasms of non-bronchial origin the procedure had a sensitivity of 42% and a significantly greater false negative rate than for primary bronchial malignancy. For the entire series 72 (40%) of the procedures failed to produce a definite diagnosis, 29 (40%) of these cases subsequently proving to be malignant. A positive diagnosis was established in only 16% of patients with benign conditions. Review of published reports and consideration of the role of this and other biopsy techniques in the investigation of discrete pulmonary lesions lead to the conclusion that needle aspiration biopsy seems particularly appropriate in the investigation of inoperable patients with probable bronchial carcinoma in whom sputum cytology and bronchoscopy do not yield a diagnosis.